Method for analyzing content of lead element in industrial silicon
By using carbon nanotube modified glass carbon electrode and DPASV method in industrial silicon, the existing analytical methods have solved the problems of low detection sensitivity and complex operation, and achieved fast, accurate and low-cost analysis of lead element content.
Patent Information
- Application Number
- CN202411185457.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2025-02-07
AI Technical Summary
The existing analysis methods for lead element content in industrial silicon have low detection sensitivity, complex operation and high cost. No DPASV-based analysis methods have been reported.
A glassy carbon electrode modified with carbon nanotubes was used, combined with differential pulse anode dissolution voltammetry (DPASV), to establish a calibration curve and quantitatively analyze the lead element in industrial silicon.
It realizes fast, accurate, simple operation and low cost determination of lead element content in industrial silicon, and has high detection sensitivity, providing a new analysis idea.
Smart Images

Figure CN119395112A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an analysis method for lead element content in industrial silicon, belonging to the technical field of chemical analysis and testing. Background Art
[0002] Industrial silicon is the most basic raw material in the silicone industry. Its quality has a great impact on the quality of silicone products. The type and content of impurity elements contained in industrial silicon are the most direct influencing factors. Lead (Pb) is one of the more common impurity elements in industrial silicon. Relevant studies have shown that when silicone monomers (i.e. dichlorodimethylsilane) are produced using silicon powder and methyl chloride as raw materials, Pb will poison the catalyst and reduce the selectivity of the monomer. In addition, silicone products are widely used in medical, interior decoration, personal care and food fields. Excessive lead residues will increase the risk of human intake of lead, which will pose a threat to human health. Therefore, the quantitative analysis of lead in industrial silicon is of great significance.
[0003] At present, the main analysis methods for lead are disulfide colorimetry, graphite furnace atomic absorption spectrometry and electrochemical ICP-OES. However, these analysis methods either have low detection sensitivity or require the use of expensive instruments and equipment and complex experimental operations. Electrochemical analysis has the advantages of fast response speed, high sensitivity and simple operation, and has been applied to the analysis and detection of heavy metal ions (such as Pb, Cu and Zn) in high-purity aluminum (GB 3828.5-1983). When electrochemically analyzing heavy metal ions, DPASV is usually used, that is, combining constant potential enrichment and dissolution with differential pulse voltammetry measurement to achieve trace analysis of heavy metal ions. At present, there is no report on the analysis method based on DPASV in the determination of Pb content in industrial silicon. Summary of the invention
[0004] In order to achieve rapid, accurate, simple and low-cost determination of the lead content in silicon powder, the present invention provides an electrochemical analysis method for the lead content in industrial silicon. After the industrial silicon block is crushed, ground and sieved, the obtained silicon powder is digested and fixed to obtain a sample solution. A glassy carbon electrode modified with carbon nanotubes is used as the working electrode, and the Pb(NO3)2 standard solution is tested by DPASV, a calibration curve is established, and the prepared sample solution is tested to complete the quantitative analysis of the Pb element in industrial silicon. The technical route provided by the present invention is simple, low-cost and has a high detection sensitivity, which provides a new idea for the detection of Pb content in industrial silicon. The specific steps are: (1) Processing of industrial silicon: The industrial silicon block is crushed and ground, then passed through a 0.149 mm sieve, and several portions of sieved silicon slag powder are weighed; (2) Digestion and sample preparation of silicon powder: Pour silicon slag powder into a sample cup, add excess nitric acid and hydrofluoric acid for digestion, add perchloric acid after digestion and evaporate until smoke appears to remove silicon, fluorine, etc., then add hydrochloric acid to dissolve the residue, and finally fix the volume with acetic acid-sodium acetate buffer solution; (3) Preparation of modified electrode: After the bare glassy carbon electrode is polished, a carbon nanotube dispersion is drop-coated on its surface and dried under an infrared lamp for later use; In the embodiments of the present application, the diameter of the bare glassy carbon electrode used is 3 mm.
[0005] (4) Determination of electrochemical analysis conditions: Turn on the electrochemical workstation (the electrochemical workstation model is CHI-660), adopt a three-electrode test system, select differential pulse anodic stripping voltammetry (DPASV), and set the electrochemical parameters and stirring rate; (5) Establish an analytical curve: 10 samples of Pb(NO3)2 standard solution with different concentrations were tested after adding a certain amount of Sb(NO3)3 solution, and the Pb 2+ The peak potential and current value of the response are established, and the current value and Pb 2+ Calibration curve of concentration; (6) Determination of lead content in industrial silicon: After adding the same amount of Sb(NO3)3 solution to the sample solution in step (2), record the content of Pb 2+ Substitute the response current value into the linear equation in step (5) and find the corresponding Pb 2+ concentration, and then calculate the Pb in industrial silicon 2+ Content; (7) Verification of the accuracy of the analytical method: Design a spike recovery experiment. In step (2), add a certain amount of Pb(NO3)2 standard solution to the digestion solution, make up the volume and shake well. According to step (6), determine the Pb in the spiked solution. 2+ The sample solution was tested using an inductively coupled plasma optical emission spectrometer (ICP-OES), and the test results were used as a control. t Test method was used to evaluate the accuracy of this analytical method.
[0006] Preferably, about 0.3500 g of silicon powder is accurately weighed using a 1 / 10,000 analytical balance.
[0007] Preferably, the sample cup used in step (2) is made of polytetrafluoroethylene and has a volume of 100 mL.
[0008] The concentration of nitric acid used in the digestion step in step (2) is 10-20 mol / L; the concentration of hydrofluoric acid used is 30-35 mol / L; the digestion temperature is 60-80°C, and the digestion time is 1-3 h; The concentration of perchloric acid used is 10-20 mol / L; the evaporation temperature is 120-130 °C; the concentration of hydrochloric acid is 5-10 mol / L; The concentration of the acetic acid-sodium acetate buffer solution used is 0.1-0.8 mol / L, pH=5.0-5.8.
[0009] Preferably, the nitric acid concentration used in the digestion step in step (2) is 14.0 mol / L; the hydrofluoric acid concentration used is 33.3 mol / L; the digestion temperature is 60 °C, and the digestion time is 2.0 h.
[0010] Preferably, the concentration of perchloric acid used in step (2) is 12.4 mol / L; the evaporation temperature is 120 °C; and the concentration of hydrochloric acid is 6 mol / L.
[0011] Preferably, the acetic acid-sodium acetate buffer solution used in step (2) has a concentration of 0.1 mol / L, a pH of 5.2, and a constant volume of 50 mL.
[0012] In step (3), the bare glassy carbon electrode is polished on suede, and the polishing agent is 0.01-0.2 μm Al2O3 slurry; The concentration of the drop-coated carbon nanotube dispersion was 1-5 mg / mL; The dispersed phase is any one of water, N,N-dimethylformamide, an aqueous solution of 0.25-0.5 mg / mL chitosan, or a DMF solution of 0.25-0.5 mg / mL chitosan.
[0013] Preferably, in step (3), the bare glassy carbon electrode is polished on suede, and the polishing agent is 0.05 μm Al2O3 slurry.
[0014] Preferably, the concentration of the carbon nanotube dispersion drop-coated in step (3) is 1 mg / mL, the volume is 5 μL, and the dispersed phase is one of water, DMF, 0.25 mg / mL chitosan aqueous solution or 0.25 mg / mL chitosan DMF solution.
[0015] Preferably, in the three-electrode system of step (4), the carbon nanotube-modified glassy carbon electrode is used as the working electrode, the Ag / AgCl electrode (saturated potassium chloride) is used as the reference electrode, and the platinum column electrode is used as the counter electrode.
[0016] Preferably, the stirring rate in step (4) is 0-60 rpm.
[0017] The parameters of DPASV in step (4) are as follows: potential range is -0.7 V to -0.4 V, amplitude is 50-80 mV, pulse period is 0.2-0.5 s, deposition potential is -1.2 to -0.8 V, and deposition time is 1 to 8 min.
[0018] Preferably, the parameters of DPASV in step (4) are set as follows: potential range is -0.7 V to -0.4 V, amplitude is 50 mV, pulse width is 0.05 s, sampling width is 0.0167 s, pulse period is 0.2 s, deposition potential is -1.2 to -0.8 V, and deposition time is 3 to 8 min.
[0019] Preferably, in step (5), the concentrations of a series of Pb(NO3)2 standard solutions are 0, 5.0×10 -9 mol / L、1.0×10 -8 mol / L、5.0×10 -8 mol / L、1.0×10 -7 mol / L、5.0×10 -7 mol / L、1.0×10 -6 mol / L、5.0×10 - 6 mol / L、1.0×10 -5 mol / L and 5.0×10 -5 mol / L.
[0020] Preferably, in step (5), the concentration of Sb(NO3)3 in the test solution is 1.0×10 -7 ~1.0×10 -6 mol / L.
[0021] Preferably, in step (5), each sample is measured three times in parallel, and the relative standard deviation of the three test values is not higher than 5%, and the average value is taken as the test result. The correlation coefficient of the linear equation (R 2 ) should be greater than 0.99.
[0022] Preferably, the calculation formula for the lead content in silicon powder in step (6) is as follows: (1) In formula (1) C Pb , V are the concentration (mol / L) and volume (L) of lead in the sample solution, M is the molar mass of lead (g / mol), m is the mass of silicon powder (g), and the unit of lead content is ppm.
[0023] Preferably, the spike recovery rate in step (7) is calculated as follows: (2) Preferably, in step (7) t The value is calculated as follows: (3) (4) In formula (3) n 1 and s 1 is the number of parallel determinations of the sample solution measured by DPASV and the standard deviation of the test results, n 2 and s 2 are the number of parallel determinations of the sample solution measured by ICP-OES and the standard deviation of the test results, s R is the combined standard deviation of the two groups of test data. In formula (4) and They are the average values of the detection results using DPASV and ICP-OES, respectively.
[0024] Compared with the prior art, the advantages and positive effects of the present invention are: (1) Compared with the conventional quantitative analysis method for Pb element in industrial silicon, the electrochemical analysis method provided by the present invention involves the use of an electrochemical workstation which has the advantages of being small in size, inexpensive and easy to operate.
[0025] (2) Carbon nanotubes have the advantages of large specific surface area and good conductivity, which can increase the effective electroactive area of the electrode and thus enhance the electrochemical detection performance. However, due to their small size and large specific surface energy, they are easy to agglomerate in solution. Compared with the aqueous phase, carbon nanotubes are more dispersible in DMF, so it can effectively solve the problem of uneven concentration of the dispersion caused by agglomeration of carbon nanotubes. In addition, due to the existence of the coffee ring effect, carbon nanotubes will still aggregate at the edge of the dried glassy carbon electrode, resulting in a decrease in the effective electroactive area of the electrode. Chitosan can not only be used as a fixing agent for carbon nanotubes to solve the problem of carbon nanotubes falling off the electrode surface, but also inhibit the coffee ring effect. Most importantly, chitosan also has a large number of hydroxyl and amino groups. As an electrode modification material, it can enhance the adhesion of Pb 2+ enrichment capacity, further improving analytical performance.
[0026] (3) During the deposition stage, Sb 3+ With Pb 2+ After reduction, Sb-Pb alloy can be formed, thereby amplifying the dissolution signal of Pb. 3+ It has low toxicity and can replace Hg commonly used in anodic dissolution method 2+ , which can prevent analysts from being exposed to Hg2+ in an environment.
[0027] (4) Industrial silicon contains many kinds of impurity elements (such as Fe, Al, Ca, Mg, Ni, Cr, P, Ti and Zn, etc.), which may cause great interference to the traditional Pb element analysis and detection methods, thereby reducing the selectivity of Pb detection. DPASV perfectly solves this problem. The impurity elements are either electrochemically inactive or their dissolution potential is far away from that of Pb, so the method has a high selectivity for detecting Pb.
[0028] (5) The electrochemical analysis speed is fast, and the Pb in the sample solution can be completed in just 5 minutes. 2+ This greatly improves the detection efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The type of carbon nanotube dispersed phase in Example 2 of the present invention is used to detect Pb by electrochemical method 2+ impact.
[0030] Figure 2 For Example 3Sb of the present invention 3+ Effect of concentration on electrochemical detection of Pb 2+ impact.
[0031] Figure 3 The effect of deposition potential on electrochemical detection of Pb in Example 4 of the present invention 2+ impact.
[0032] Figure 4 The effect of deposition time on electrochemical detection of Pb in Example 5 of the present invention 2+ impact.
[0033] Figure 5 The interference of Example 6 in the present invention on the electrochemical detection of Pb 2+ impact.
[0034] Figure 6 The DPASV curves of a series of Pb(NO3)2 standard solutions tested in Example 7 of the present invention.
[0035] Figure 7 A series of Pb(NO3)2 standard solutions were tested for Example 7 of the present invention. 2+ Calibration curve of concentration and current value.
[0036] The present invention is further described below in conjunction with the accompanying drawings and specific implementation modes, but the protection scope of the present invention is not limited to the following implementation modes. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is described in detail below.
[0038] Unless otherwise specified, the reagents and materials used in the following examples can be purchased on the market.
[0039] The experimental methods and detection methods used in the examples are conventional methods unless otherwise specified.
[0040] Example 1 This embodiment provides steps for processing industrial silicon blocks and preparing spiked solutions for samples, and the specific process is as follows: Four different batches of industrial silicon blocks were crushed and ground, and then sieved with a 0.149 mm sieve. The sieved silicon slag powder was accurately weighed with a mass of about 0.3500 g and placed in a polytetrafluoroethylene sample cup. Nitric acid (6.0 mL, 14.0 mol / L) and hydrofluoric acid (2.0 mL, 33.3 mol / L) were added in sequence and heated to 60 °C for 2.0 h. After the digestion, perchloric acid (3.0 mL, 12.4 mol / L) was added and heated to 120 °C and evaporated until smoke appeared. Hydrochloric acid (2.0 mL, 6 mol / L) was added to dissolve the residue, and the digestion solution was fixed to 50 mL with acetic acid-sodium acetate buffer solution (pH=5.2, 0.1 mol / L).
[0041] In the preparation process of the spiked solution of the sample, except for adding Pb(NO3)2 standard solution (1.0 mL, 5.0×10 - 6 mol / L or 2.5×10 -5 mol / L), and the others remain unchanged.
[0042] Example 2 The following test was continued using the sample treated in Example 1: This example provides a method for preparing a carbon nanotube modified electrode and explores the effect of dispersion type on the Pb 2+ The specific steps of electrochemical detection are as follows: After the glassy carbon electrode (3 mm in diameter) was polished 30 times in the shape of "8" on the suede, it was ultrasonically cleaned with deionized water for 20 s. Turn on the electrochemical workstation CHI-660, adopt a three-electrode test system, use the glassy carbon electrode as the working electrode, the Ag / AgCl electrode (saturated potassium chloride) as the reference electrode, and the platinum column electrode as the counter electrode, and connect the corresponding wires. Select cyclic voltammetry, set the potential scanning range to -0.2~0.6 V, the scanning speed to 50 mV / s, and keep the other parameters as default. In the measured curve, if the difference between the oxidation potential and the reduction potential is not higher than 100 mV, it means that the electrode has been polished smoothly, otherwise it should be re-polished and ultrasonically cleaned. On the polished electrode surface, a carbon nanotube dispersion (5 μL, 1 mg / mL) was added dropwise. The dispersed phase was water, DMF, and an aqueous solution of 0.25 mg / mL chitosan ( Figure 1 chitosan / water) or 0.25 mg / mL chitosan in DMF ( Figure 1 The mixture is expressed as chitosan / DMF in the above formula (expressed as chitosan / DMF), and dried under infrared light for later use.
[0043] Turn on the electrochemical workstation, connect the working electrode, platinum column electrode and Ag / AgCl saturated potassium chloride electrode, and place the three-electrode system in a 5.0×10 -7 mol / L Sb(NO3)3 and 1.0×10 -7 mol / L Pb(NO3)2 in acetic acid-sodium acetate buffer solution (0.1 mol / L, pH=5.2), with a stirring rate of 30 rpm. The DPASV parameter settings are as follows: deposition potential, -1.0 V; deposition time, 5 min; standing time, 20 s; potential range, -0.7~-0.4 V; amplitude, 50 mV; pulse width, 0.05 s; sampling width, 0.0167 s; pulse period, 0.2 s; each electrode was measured three times, and its response potential and response current values were recorded.
[0044] The results are as follows Figure 1 As shown in the figure, when 0.25 mg / mL chitosan in DMF solution is used as dispersed phase, Pb 2+ The response current value is relatively high, and the deviation of the three test results is small. Other test data also have significant effects.
[0045] Example 3 Based on Example 2, this example provides the effect of Sb(NO3)3 concentration on Pb 2+ The specific steps of electrochemical detection are as follows: The carbon nanotube dispersion (5 μL, 1 mg / mL) used in this example is a 0.25 mg / mL chitosan DMF solution as the dispersed phase, and the preparation steps of the working electrode are the same as those in Example 2. -7 mol / L Pb(NO3)2, the concentration of Sb(NO3)3 is 1.0×10 -7 ~1.0×10 -6 mol / L, and the other test conditions were the same as in Example 2. The results are shown in Figure 2 As shown in the figure, when the concentration of Sb(NO3)3 is 3.0~7.0×10 -7 mol / L, Pb 2+ The response current values of Sb 3+ Can be used with Pb 2 + The formation of Sb-Pb alloy on the electrode surface can greatly amplify the dissolution signal of Pb.
[0046] Example 4 This example provides the effect of deposition potential on Pb 2+ The specific steps of electrochemical detection are as follows: In this embodiment, the concentration of Sb(NO3)3 is 5.0×10 -7 mol / L, the deposition potential is -1.2~-0.8 V, and the preparation and testing conditions of the working electrode are the same as those in Example 3. The results are shown in Figure 3 As shown, when the deposition potential is -1.0 V, Pb 2+ The response current value is the highest and the deviation of the detection result is ideal.
[0047] Example 5 This example provides the effect of deposition time on Pb 2+ The specific steps of electrochemical detection are as follows: In this embodiment, the concentration of Sb(NO3)3 is 5.0×10 -7 mol / L, the deposition time is 1-8 min, and the preparation and testing conditions of the working electrode are the same as those in Example 3. Figure 4 As shown in Figure 2, when the deposition time is 5 min, Pb 2+ The response current value increases to the maximum and tends to equilibrium, indicating that Pb 2+ The enrichment and reduction effect is optimal.
[0048] Through Examples 2 to 5, it was determined that the DPASV method was used to detect Pb 2+ The optimal conditions are: the carbon nanotube dispersion phase is 0.25 mg / mL chitosan in DMF solution, the concentration of Sb(NO3)3 is 5.0×10 -7mol / L, the deposition potential was -1.0 V, and the deposition time was 5 min. The electrochemical tests in the subsequent examples were all conducted under this condition.
[0049] Example 6 This example provides interference of interfering substances on electrochemical detection of Pb(NO3)2 solution, and the specific steps are as follows: Take one or more of NaF, KCl, NaCl, KH2PO4, Fe(NO3)3, Al(NO3)3, Ca(NO3)2, Mg(NO3)2, Ni(NO3)2, Cr(NO3)3 and Zn(NO3)2 as interferences, weigh a certain mass of interferences and add them to the Pb(NO3)2 solution so that its molar concentration is 10 times that of Pb(NO3)2. The test results are as follows Figure 5 As shown, after adding the interferent, Pb 2+ The current value fluctuation does not exceed 2%, indicating that the analysis method has good anti-interference ability.
[0050] Example 7 This embodiment provides a series of electrochemical tests of Pb(NO3)2 standard solutions and the establishment of calibration curves, and the specific steps are as follows: In this embodiment, the preparation and testing conditions of the working electrode were the same as those in Example 5. A series of Pb(NO3)2 standard solutions (0, 5.0×10 -9 mol / L、1.0×10 -8 mol / L、5.0×10 -8 mol / L、1.0×10 -7 mol / L、5.0×10 -7 mol / L、1.0×10 -6 mol / L、5.0×10 -6 mol / L、1.0×10 -5 mol / L and 5.0×10 -5 mol / L) for measurement, the electrochemical test curve is as follows Figure 6 As shown. Draw Pb 2+ The calibration curve of concentration (x) and response current (y) was calculated at 5.0×10 -9 ~5.0×10 - 6 mol / L concentration range, the linear equation is y=5.5615x+0.0576, R 2 =0.9967( Figure 7 ). The detection limit is 3 times the signal-to-noise ratio (S / N), which is calculated to be 1.2×10 -9 mol / L.
[0051] Example 8 This example provides the Pb content of the sample solution and the spiked solution. 2+ The specific steps for electrochemical determination of concentration are as follows: The three-electrode system was used to detect the sample solution prepared in Example 1 and its spiked solution. The measured Pb 2+ The response current value is substituted into the linear equation and the corresponding concentration is calculated. As shown in Table 1, after testing, the Pb in the 4 sample solutions 2+ The concentrations were 2.81×10 -7 mol / L、3.12×10 -7 mol / L、2.56×10 -7 mol / L and 3.32×10 -7 mol / L. According to formula (1), the content of lead in four samples of industrial silicon was calculated to be 8.2 ppm, 9.0 ppm, 7.4 ppm and 9.7 ppm respectively. In the spike recovery experiment, according to formula (2), the recovery rate was calculated to be 91.0%~107%, indicating that the analytical method has good practicality.
[0052] Table 1 Data of lead content in industrial silicon measured by the present invention.
[0053] sample Weighing mass (g) Constant volume (L) <![CDATA[Pb 2+ Detection concentration (10 -6 mol / L)]]> Pb content (ppm) 1 0.3527 0.050 0.281 8.2 2 0.3586 0.050 0.312 9.0 3 0.3503 0.050 0.252 7.4 4 0.3543 0.050 0.332 9.7 Verification Example 1 This verification example provides the Pb content in the sample solution and the spiked solution. 2+ The ICP-OES determination results of the concentration are as follows: According to GB / T 14849.4-2014 "Chemical Analysis Methods for Industrial Silicon", ICP-OES was used to analyze the Pb in the sample solution. 2+ The test conditions are: Instrument: Inductively coupled plasma optical emission spectrometer (Agilent); Power: 1300 W; Plasma gas flow rate: 14.0 L / min; Auxiliary gas flow rate: 0.3 L / min; Atomizing gas flow rate: 0.6 L / min.
[0054] As shown in Table 2, the Pb content in the four sample solutions 2+ The concentrations were 2.63×10 -7 mol / L、2.94×10 -7 mol / L、2.70×10 -7 mol / L and 3.15×10 -7 mol / L. Using the ICP-OES test results as a control, tTest method, according to formula (3) and (4), the t value is calculated to be lower than t crit [0.05, 4]=2.78, indicating that there is no significant difference in the detection results of the two methods, proving that the electrochemical analysis method provided in the present invention has satisfactory accuracy.
[0055] Table 2 Pb in sample solution and spiked solution detected by electrochemical method and ICP-OES in the present invention 2+ Concentration data:
[0056] The above is only a preferred embodiment of the present invention and does not limit the present invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes and apply it to other fields. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention is still protected by the technical solution of the present invention.
Claims
1. A method for analyzing the content of lead in industrial silicon, characterized in that: The specific steps are as follows: (1) Processing of industrial silicon: The industrial silicon blocks are crushed and ground, then passed through a sieve, and several portions of sieved silicon slag powder are weighed; (2) Digestion and sample preparation of silicon powder: Pour silicon slag powder into a sample cup, add excess nitric acid and hydrofluoric acid for digestion, add perchloric acid after digestion and evaporate until smoke appears to drive off silicon and fluorine, then add hydrochloric acid to dissolve the residue, and finally make up the volume with acetic acid-sodium acetate buffer solution; (3) Preparation of modified electrode: After the bare glassy carbon electrode is polished, a carbon nanotube dispersion is drop-coated on its surface and dried under an infrared lamp for later use; (4) Determination of electrochemical analysis conditions: Turn on the electrochemical workstation, use the three-electrode test system, select differential pulse anodic stripping voltammetry, and set the electrochemical parameters; (5) Establish an analytical curve: 10 samples of Pb(NO3)2 standard solution with different concentrations were tested after adding a certain amount of Sb(NO3)3 solution, and the Pb 2+ The peak potential and current value of the response are established, and the current value and Pb 2+ Calibration curve of concentration; (6) Determination of lead content in industrial silicon: After adding the same amount of Sb(NO3)3 solution to the sample solution in step (2), record the content of Pb 2+ Substitute the response current value into the linear equation in step (5) and find the corresponding Pb 2+ concentration, and then calculate the Pb in industrial silicon 2+ Content; (7) Verification of the accuracy of the analytical method: Design a spike recovery experiment. In step (2), add a certain amount of Pb(NO3)2 standard solution to the digestion solution, make up the volume and shake well. According to step (6), determine the Pb in the spiked solution. 2+ concentration and calculate the spike recovery; The sample solution was tested using an inductively coupled plasma optical emission spectrometer (ICP-OES), and the test results were used as a control. t Test method was used to evaluate the accuracy of this analytical method.
2. The method for analyzing the content of lead in industrial silicon according to claim 1, characterized in that: The concentration of nitric acid used in the digestion step in step (2) is 10-20 mol / L; the concentration of hydrofluoric acid used is 30-35 mol / L; the digestion temperature is 60-80°C, and the digestion time is 1-3 h; The concentration of perchloric acid used is 10-20 mol / L; the evaporation temperature is 120-130 °C; the concentration of hydrochloric acid is 5-10 mol / L; The concentration of the acetic acid-sodium acetate buffer solution used is 0.1-0.8 mol / L, pH=5.0-5.
8.
3. The method for analyzing the content of lead in industrial silicon according to claim 1, characterized in that: In step (3), the bare glassy carbon electrode is polished on suede, and the polishing agent is 0.01-0.2 μm Al2O3 slurry; The concentration of the drop-coated carbon nanotube dispersion was 1-5 mg / mL; The dispersed phase is any one of water, N,N-dimethylformamide, an aqueous solution of 0.25-0.5 mg / mL chitosan, or a DMF solution of 0.25-0.5 mg / mL chitosan.
4. The method for analyzing the content of lead in industrial silicon according to claim 1, characterized in that: In the three-electrode system of step (4), the carbon nanotube-modified glassy carbon electrode is used as the working electrode, the Ag / AgCl electrode is used as the reference electrode, and the platinum column electrode is used as the counter electrode; During the detection in step (4), stirring is also performed, wherein the stirring rate is 0-60 rpm.
5. The method for analyzing the content of lead in industrial silicon according to claim 1, characterized in that: The parameters of DPASV in step (4) are as follows: potential range is -0.7 V to -0.4 V, amplitude is 50-80 mV, pulse period is 0.2-0.5 s, deposition potential is -1.2 to -0.8 V, and deposition time is 1 to 8 min.
6. The method for analyzing the content of lead in industrial silicon according to claim 1, characterized in that: In step (5), a series of Pb(NO3)2 standard solutions were prepared with concentrations of 0, 5.0×10 -9 mol / L、1.0×10 -8 mol / L、5.0×10 -8 mol / L、1.0×10 -7 mol / L、5.0×10 -7 mol / L、1.0×10 -6 mol / L、5.0×10 -6 mol / L、1.0×10 -5 mol / L and 5.0×10 -5 mol / L.
7. The method for analyzing the content of lead in industrial silicon according to claim 1, characterized in that: In step (5), the concentration of Sb(NO3)3 in the test solution is 1.0×10 -7 ~1.0×10 -6 mol / L.
8. The method for analyzing the content of lead in industrial silicon according to claim 1, characterized in that: The calculation formula for the lead content in silicon powder in step (6) is as follows: (1) In formula (1) C Pb , V are the concentration (mol / L) and volume (L) of lead in the sample solution, M is the molar mass of lead (g / mol), m is the mass of silicon powder (g), and the unit of lead content is ppm.
9. The method for analyzing the content of lead in industrial silicon according to claim 1, characterized in that: The calculation of the spike recovery in step (7) is as follows: (2)。 10. The method for analyzing the content of lead in industrial silicon according to claim 9, characterized in that: In step (7) t The value is calculated as follows: (3) (4) In formula (3) n 1 and s 1 is the number of parallel determinations of the sample solution measured by DPASV and the standard deviation of the test results, n 2 and s 2 are the number of parallel determinations of the sample solution measured by ICP-OES and the standard deviation of the test results, s R is the combined standard deviation of the two groups of test data; in formula (4) and They are the average values of the detection results using DPASV and ICP-OES, respectively.
Citation Information
Patent Citations
Preparation method of electrochemical sensor for trace lead ion detection
CN108982641A
Method for detecting lead ion content of industrial wastewater based on electrochemical sensor
CN110927236A
Preparation of composite modified electrode and method for simultaneously determining trace cadmium ions and lead ions
CN111157597A